Surgical Site and Blood Stream Infections in Children with Delayed Sternal Closure after Cardiopulmonary Bypass Surgery: A Single-Center Experience - Hubara, Evyatar; Serencev, Irena; Kriger, Or; Rachel, Shatzman Steuerman; Keizman, Eitan; Nellis, Marianne E.; Mishali, David; Lerner, Reut Kassif; Katz, Uriel; Skorchin, Yelena; Barkai, Galia; Pessach, Itai (Journal of Pediatric Infectious Diseases, 2023)
Objective Delayed sternal closure (DSC) is a frequent strategy for optimizing hemodynamics for patients after complicated cardiac surgery. However, this practice is associated with increased risk for infection and mortality. Despite the importance of antibiotic prophylaxis during open chest management, no clear recommendations are available. We sought to describe our practice with single-agent prophylactic antibiotic treatment for children with DSC.Methods We retrospectively reviewed the electronic medical record of children with delayed chest closure after stage 1 palliative surgery, between January 2009 and December 2020. Demographics, antibiotic treatment, and data regarding postoperative infection occurrence were collected. The primary outcomes were surgical site infection (SSI) and blood stream infection (BSI) rates within 28 days of repair.Results Sixty-eight patients were identified with single ventricle physiology, who underwent Damus–Kaye–Stansel or a modified Norwood procedure, remained with an open chest postoperatively, and were treated with prophylactic cefazolin. Sixty-three percent (43/68) of the children were male with a median (interquartile range) age of 9 (6–16) days. Eleven patients (16%) had an SSI or BSI identified postoperatively. Those with infections were significantly older (8 vs. 14 months, p = 0.037), had longer central line time (11 vs. 7 days, p = 0.004), had a central line location other than internal jugular (p = 0.022), and had a dialysis line (p = 0.022).Conclusion Our study demonstrates a relatively low occurrence rate of postoperative SSIs and bacteremia with prophylactic cefazolin therapy among children with DSC suggesting that single-agent, narrow antimicrobial treatment may be sufficient in this high-risk population.
Keywords: antibiotic prophylaxis; cardiopulmonary bypass; pediatrics; surgical site infection; delayed chest closure